REDISAIN INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) RUMAH SAKIT UMUM DAERAH (RSUD) TIMIKA, PAPUA - Setiyono, Setiyono; Rahardjo, Petrus Nugro (Center for Environmental Technology, 2010)
Hospital is playing an important role in serving people who need to get health. On the other hand its occurrence causes some problems as well. One of them is the infectious wastewaters which are potential to cause a dangerous effect for human life. A lot of hospitals in Indonesia do not have the proper wastewater treatment plant yet. The local hospital of County Timika has already had a wastewater treatment plant (WWTP), but until now the capacity of the unit can not fulfil the required level of environmental standard yet. One of the problems is the technically improper treatment processes. To solve the problems, the WWTP must be redesigned and modifief by using a combination technique of anaerobik and aerobic biofilter treatment processes.The newly proposed design process of WWTP for the local hospital in TImika has already prepared to be applied.Ã‚Â Keywords : Medical Wastewater Treatment Process, anerobic/aerobic biofilterÃ‚Â